Exploring the Ecotourism Potential of Mangrove Ecosystems: A Case Study of Bhadrika Mangrove Tourism Park for Sustainable Coastal Development in Indonesia - Riana, Anike; Okta Pianti, Dinsi; Ramadhila, Rizka; Pranata, Yokos; Rangga Nata, Penggi (ISEJ : Indonesian Science Education Journal, 2023)
This study explores the ecotourism potential of the Bhadrika Mangrove Tourism Park in Bengkulu, Indonesia, with the aim of assessing its attractiveness as a sustainable tourism destination that can contribute to both environmental conservation and local economic development. The research was conducted in July-August 2020, utilizing a mixed-methods approach that combined field observations and semi-structured interviews with local stakeholders, community members, and visitors. The data were analyzed using descriptive methods and the Scenic Beauty Estimation (SBE) technique to evaluate the aesthetic appeal of the park’s mangrove ecosystems. The results revealed that the park’s diverse mangrove species, river estuaries, and coastal landscapes offer significant potential for educational and recreational tourism activities. Key attractions include guided tours, photography zones, children’s play areas, and local food vendors. The study also highlighted strong community support for ecotourism, with local residents expressing interest in participating in tourism-related activities and benefiting from increased job opportunities. Despite the promising potential, the study identified several challenges, including the need for infrastructure improvements and the importance of maintaining a balance between tourism growth and ecological preservation. This research contributes to the growing body of knowledge on mangrove ecotourism by providing a detailed case study of a lesser-known mangrove site in Indonesia. The findings suggest that with appropriate management, the Bhadrika Mangrove Tourism Park could serve as a model for sustainable ecotourism in coastal regions, promoting both conservation and community empowerment.